Analytic Hierarchy Process to choose the cement type to protect reinforced concrete to corrosion caused by chloride ions attack - Lopes da Silva, S. H.; Londero, C.; Medeiros, M. H. F.; Pereira, V. C. O.; Monteiro, E. C. B. (Revista ALCONPAT, 2015)
This paper discuss cement types combinations to obtain the best one to protect against the steelreinforcement corrosion caused by chloride ions. In this case, it was used the method of AnalyticHierarchy Process (AHP), which is based on the definition of the main elements for making fast,reliable and objective decision. Three types of cement (CPII-Z-32: pozzolanic admixture, CPIII-40:blast furnace slag admixture and CPIV-32: pozzolanic admixture), two water/cement ratio (0,4 and0,7) and two curing times (7 and 28 days), were analyzed trough results of five experiments. Theapplication of AHP was effective to choose the type of cement, concluding that the CPIII-40 cementshowed the best performance compared to the other cements.Keywords: Analytical hierarchy process. Reinforced concrete. Steel corrosion.